Learning Process Management in Post-Pandemic Early Childhood Education - Fuadaturrahmah, Fuadaturrahmah; Ahmad Al Munawar (Journal Management of Sport, 2023)
This study aims to analyze the management of the learning process of Early Childhood Education (ECE) after the COVID-19 pandemic in Medan City, North Sumatra Province, Indonesia. The research approach used is descriptive qualitative. The results showed that the 4 functions of learning process management can be carried out even with several obstacles in formal and non-formal Early Childhood Education institutions. There are differences in the learning process during the COVID-19 pandemic and Post-Pandemic, namely the use of blended learning methods by combining online and offline learning. The application of health protocols is also an integral part of the learning carried out by Early Childhood Education institutions. Suggestions for further research include management analysis on other Early Childhood Education standards to provide a comprehensive picture of the impact of the COVID-19 pandemic on Early Childhood Education and become input for policymakers to establish education policies during the COVID-19 post-pandemic (New Normal).